Anabolic androgenic steroids: Part II - Haff, G. G. (Strength and Conditioning Journal, 2007)
Question 7: Are there clinical applications for anabolic steroids in contemporary medicine? If so, can you offer some indications for their legitimate use? Question 8: Generally, athletes take suprapharmacological dosages of steroids and often take multiple drugs (i.e., "stacking"). Can you give any insight into these practices, including an athlete's motivation to stack drugs, efficacy, and adverse effects? Question 9: How effective are the most rigorous current drug testing procedures (e.g., World Anti-Doping Agency [WADA], United States Anti-Doping Agency [USADA]) at controlling illicit drug use? Question 10: Recently the designer steroids, THG and DMT, were uncovered. In your opinion, are there more steroids that might not be presently detectable that have yet to be discovered? Question 11: Many times athletes claim that positive tests for anabolic steroids occur as a result of contaminated dietary supplements. In your opinion, is this a legitimate consideration for a false-positive drug test? Question 12: What are some of the performance-enhancing substances, practices, and/or techniques that are on the horizon (e.g., gene doping)? Question 13: Historically, the issue of steroid use has produced dichotomous positions: one group recommends that steroid use be legalized, while the other suggests that more stringent drug testing is needed. In your opinion, what are the perceived justifications and ramifications for such divergent schools of thought?